2023
DOI: 10.1002/ajpa.24796
|View full text |Cite
|
Sign up to set email alerts
|

Morphological variation of the Pan talus relative to that of Gorilla

Christine M. Harper,
Caleigh S. Roach,
Deanna M. Goldstein
et al.

Abstract: Objectives Differences in talar articular morphology relative to locomotion have recently been found within Pan and Gorilla. Whole‐bone talar morphology within, and shared variation among, Pan and Gorilla (sub)species, however, has yet to be investigated. Here we separately analyze talar external shape within Pan (P. t. troglodytes, P. t. schweinfurthii, P. t. verus, P. paniscus) and Gorilla (G. g. gorilla, G. b. beringei, G. b. graueri) relative to degree of arboreality and body size. Pan and Gorilla are addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 118 publications
0
0
0
Order By: Relevance
“…Postcranial variation among gorilla taxa has been extensively studied over recent years (e.g., Fatica et al, 2019; Jabbour & Pearman, 2016; Ruff et al, 2022; Ruff, Burgess, Junno, et al, 2018; Ruff, Burgess, Squyres, et al, 2018), with many studies focusing on external morphological variation in the foot and ankle (e.g., Dunn et al, 2014; Harper et al, 2021b, 2023; Jabbour & Pearman, 2016; Knigge et al, 2015; Prang & Tocheri, 2024; Tocheri et al, 2011). These studies have found many differences among the taxa with respect to locomotor repertoires, such as relatively shorter feet in G. b. beringei for greater terrestriality and more asymmetric talar trochlear rims in G. g. gorilla , which has been suggested to reduce shearing stresses when the foot is loaded on uneven substrates as an adaptation for arboreality (Dunn et al, 2014; Harper et al, 2023; Inouye, 1992; Jabbour & Pearman, 2016; Knigge et al, 2015; Ruff et al, 2022; Ruff, Burgess, Junno, et al, 2018; Ruff, Burgess, Squyres, et al, 2018; Schultz, 1934; Tocheri et al, 2011). There are many morphological differences in calcaneal external morphology among the taxa including a flatter calcaneocuboid joint with a shallower cuboid facet pivot region and a mediolaterally wider calcaneal tuber in the more terrestrial G. b. beringei (Harper et al, 2021b; Jabbour & Pearman, 2016; Prang & Tocheri, 2024).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Postcranial variation among gorilla taxa has been extensively studied over recent years (e.g., Fatica et al, 2019; Jabbour & Pearman, 2016; Ruff et al, 2022; Ruff, Burgess, Junno, et al, 2018; Ruff, Burgess, Squyres, et al, 2018), with many studies focusing on external morphological variation in the foot and ankle (e.g., Dunn et al, 2014; Harper et al, 2021b, 2023; Jabbour & Pearman, 2016; Knigge et al, 2015; Prang & Tocheri, 2024; Tocheri et al, 2011). These studies have found many differences among the taxa with respect to locomotor repertoires, such as relatively shorter feet in G. b. beringei for greater terrestriality and more asymmetric talar trochlear rims in G. g. gorilla , which has been suggested to reduce shearing stresses when the foot is loaded on uneven substrates as an adaptation for arboreality (Dunn et al, 2014; Harper et al, 2023; Inouye, 1992; Jabbour & Pearman, 2016; Knigge et al, 2015; Ruff et al, 2022; Ruff, Burgess, Junno, et al, 2018; Ruff, Burgess, Squyres, et al, 2018; Schultz, 1934; Tocheri et al, 2011). There are many morphological differences in calcaneal external morphology among the taxa including a flatter calcaneocuboid joint with a shallower cuboid facet pivot region and a mediolaterally wider calcaneal tuber in the more terrestrial G. b. beringei (Harper et al, 2021b; Jabbour & Pearman, 2016; Prang & Tocheri, 2024).…”
Section: Introductionmentioning
confidence: 99%
“…Postcranial variation among gorilla taxa has been extensively studied over recent years (e.g., Fatica et al, 2019;Jabbour & Pearman, 2016;Ruff et al, 2022;Ruff, Burgess, Squyres, et al, 2018), with many studies focusing on external morphological variation in the foot and ankle (e.g., Dunn et al, 2014;Harper et al, 2021bHarper et al, , 2023Jabbour & Pearman, 2016;Knigge et al, 2015;Prang & Tocheri, 2024;Tocheri et al, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Weighted spherical harmonics (SPHARM) is one such method to effectively analyze the shape of small, irregularly shaped objects, such as the talus. [33][34][35] This method has been implemented by previous studies to examine variation in tarsal shape in both humans and primates. 34,36 Additionally, a statistical description of the distribution of bone density that investigates sex and age variation will be advantageous to implant design.…”
mentioning
confidence: 99%
“…[33][34][35] This method has been implemented by previous studies to examine variation in tarsal shape in both humans and primates. 34,36 Additionally, a statistical description of the distribution of bone density that investigates sex and age variation will be advantageous to implant design. With such information, surgical devices such as total ankle replacements could be further customized for a patient's specific age and sex, potentially resulting in an increase in implant success.…”
mentioning
confidence: 99%